Clinical aspects encountered in patients with portopulmonary hypertension - Bulacu-Durand, Patricia; Biciusca, Viorel; Cazacu, Sergiu-Marian; Stan, Sorina Ionelia; Ciobanu, Petre; Boldeanu, Mihail-Virgil; Bezna, Maria Cristina; Istratoaie, Octavian (Medicine and Pharmacy Reports, 2025)
Portopulmonary hypertension (PoPH) is a condition characterized by the elevation of the arterial pulmonary pressure because of portal hypertension which leads to right heart failure and finally death. The most common cause of PoPH is hepatic cirrhosis, but patients with non-cirrhotic portal hypertension can also develop this complication. It is considered that between 2% and 10% of patients with portal hypertension can develop PoPH, and it is a major determinant factor of prognosis, especially in the context of liver transplantation. Clinically, the symptoms are nonspecific and are usually due to worsening right ventricular dysfunction. The treatment of PoPH consists of vasomodulating therapy, but several future challenges remain in the treatment of PoPH patients. In the absence of medical treatment or liver transplantation, the 1-year survival rate is 35%-46% and 5-year survival rate is 4-14%. Despite advances in understanding this disease, several unresolved questions remain regarding screening, diagnosis, treatment, and liver transplantation.